Investigating the relationships between land use characteristics, public transport network features and financial viability at a corridor scale - Cooke, Sean (Department of Civil Engineering, 2017)
The successful integration of public transport and land development planning is likely to be central in determining how effectively the cities in the 'global south' manage the mounting pressures from rapid urbanization, population growth and rising income inequality. While a number of Sub-Saharan African cities, particularly in South Africa, have commenced large scale public transport reform, little research has been undertaken to date on appropriate public transport-land use integration in these contexts. As a result, both of the initial phases of BRT corridor implementation, in Cape Town and Johannesburg, have been found to be financially unsustainable in their current urban forms. The major decisions regarding the design of land use environments and public transport networks, in the context of rapidly developing cities, still occur without due consideration for each other. The aim of this study is to investigate the relationships between land use characteristics, network features and viable public transport services in the South African context and at a corridor scale. The study utilises a public transport corridor operating cost model that was created to simulate the effects of variation in four land use characteristics (population density, density distribution, land use mix and destination accessibility) and two public transport network features (mode technology and service configuration) on the financial viability of services. The corridor operating cost model consists of cascading land use, transport and costing sub-models for which the output of one supplies the input of the next. Gross population density was found to have the weakest causal relationship with financial viability. Density distribution was shown to have a very significant effect on the average passenger trip length, and financial viability as a result. When the majority of the population is articulated adjacent to the public transport trunk corridors, at a higher density, far fewer inefficient feeder services are required. Additionally, the chosen non-motorised transport mode for those accessing the trunk service directly had a considerable effect as the higher speed of bicycles increases the catchment area within which a feeder service is usually not required. Bicycle-based density articulation was able to halve the total cost of the public transport network in one of the cases, relative to the conventional pedestrian-based variety. Land use mix had a strong connection to public transport financial viability, through substantial effects on peak passenger volume. The final land use characteristic, destination accessibility, was represented by distance to the Central Business District (CBD), as well as dictating the length of the transport corridor. It was found to have a substantial influence on financial viability and affordability, especially in the context of a distance-based fare system. Passenger volume is the key determinant of mode technology choice and is influenced by population density, as well as the other three land use characteristics to a lesser degree. Low population densities intuitively favour smaller vehicles, while high densities or economies of scale promote the use of suburban rail and other capital intensive modes. Long public transport corridors with unsupportive land use environments favour larger vehicles, such as the BRT and non-BRT articulated bus modes. Fewer of these large vehicles are required to meet the demand and they can efficiently operate over longer distances than their smaller competitors. Whereas, short corridors and supportive land use environments favour the space priority that the conventional and articulated BRT modes possess. The higher speed that the segregated lanes allow the vehicles to reach over the shorter route distance also decreases vehicle requirements due to the higher rate of trips per hour per vehicle. The trunk-feeder and direct service configurations reacted similarly to the changes in land use characteristics, when the optimum modes are chosen to minimise costs. The results of the study suggest that a detailed land use development plan is necessary for each major public transport corridor, with unique targets for population density, density articulation and land use mix. It also demonstrated that, in the South African context, to achieve a high public transport modal split and sustainable public transport service requires high population densities, high articulation, mixed land uses, small corridor catchment areas and minimal feeder services.